TANAWWU’ AL-LAKSIMAT AL-‘ARABIYYAT SLANK: DIRASAT HALAT ‘AN AL-LAHJAT AL-‘ARABIYYAT AL-SU’UDIYYAT WA AL-LAHJAT AL-‘ARABIYYAT AL-MISHRIYYAT - Lillah, Furna Khubbata; Bugis, Muna Muliadi Siming (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2023)
Dialectology is an interdisciplinary study in linguistics that examines various aspects of language variation. The emergence of dialects often presents a barrier to communication among speakers with different language backgrounds. Therefore, this research is important as a reference for foreign speakers to understand Arabic dialects and can serve as an academic resource for researchers specializing in Arabic linguistics. This study aims to describe the diversity in Saudi Arabian Arabic and Egyptian Arabic dialects and describe the forms and examples of usage of Saudi Arabian Arabic and Egyptian Arabic dialects in informal conversations. The research used a qualitative approach with interview techniques. The data source for this research was native speakers of Saudi Arabian and Egyptian Arabic, and data collection and analysis were performed using note-taking methods. The data analysis involved classifying primary data according to Arabic dialect variations. The research results showed that the existence of variation in Saudi Arabian Arabic and Egyptian Arabic dialects in several aspects, including phonological variation in vowel and consonant sounds, morphological variation such as inflection, derivation, and affixation in past and present tense verbs, syntactic variation, and finally, onomasiological and semasiological variation in Saudi Arabian and Egyptian Arabic dialects. There are forms and examples of the usage of Saudi Arabian Arabic and Egyptian Arabic dialects in informal conversations.or what called idiom.